2002
DOI: 10.1093/annonc/mdf170
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial injury revealed by plasma troponin I in breast cancer treated with high-dose chemotherapy

Abstract: In our population, the elevation of TnI soon after HDC accurately predicts the development of future LVEF depression. In this setting, TnI can be considered a sensitive and reliable marker of myocardial damage with relevant clinical and prognostic implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
164
1
7

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(175 citation statements)
references
References 27 publications
3
164
1
7
Order By: Relevance
“…Differentiation between "normal" and "clinically relevant" functional impairment was made by considering as a pathologic value a decrease in LVEF below the 10th percentile of the distribution of the changes of LVEF. According to previous experience (21,26 ), values below the 10th percentile are associated with clinically relevant decreases in ejection fraction (27 ).…”
Section: Discussionmentioning
confidence: 94%
“…Differentiation between "normal" and "clinically relevant" functional impairment was made by considering as a pathologic value a decrease in LVEF below the 10th percentile of the distribution of the changes of LVEF. According to previous experience (21,26 ), values below the 10th percentile are associated with clinically relevant decreases in ejection fraction (27 ).…”
Section: Discussionmentioning
confidence: 94%
“…Cardiac troponins are sensitive markers of myocardial injury with both troponin I (Tn-I) and T (Tn-T) assays. Cardinale et al demonstrated that the timing and degree of Tn-I rise was predictive of developing LV dysfunction, and also correlated with anthracycline cumulative dosing [43][44][45][46]. Tn-I monitoring also served effectively as risk stratification in their studied population; patients treated with high-dose chemotherapy who developed an increased in Tn-I were the ones who benefited more from the initiation of an angiotensin-converting enzyme inhibitor treatment (enalapril), preventing LVEF decrease [47].…”
Section: Circulating Biomarkersmentioning
confidence: 99%
“…In regards to biomarkers, troponin levels appear to have the best predictive value in detecting cardiotoxicity monitoring, with the timing and the degree of the rise correlated with risk of CTRCD [43][44][45][46]. Troponin elevations during treatment also identify a high risk cohort of cancer patients who may benefit from early cardioprotective medication [47].…”
Section: Proposed Multimodality Imaging Strategiesmentioning
confidence: 99%
“…The clinical application of cardiac troponins as cardiotoxicity biomarkers was analyzed in 7 clinical studies with a consistent number of subjects (> 40 patients enrolled) monitored by cardiac troponin I (cTnI) or cardiac troponin T (cTnT), for the total number of almost 1 500 adult patients treated with CT for cancer [34][35][36][37][38][39][40]. See Table 2.…”
Section: Cardiac Troponins As Markers Of Ct-induced Cardiotoxicitymentioning
confidence: 99%